Extraction of various fish gelatin assisted by High Pressure Processing (HPP) - Yusof, Nurlina; Jaswir, Irwandi; Jamal, Parveen; Jami, Mohammed Saedi (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)

(untitled)
Gelatin from fish skin is known to be an alternative source for mammalian gelatin. However, it has weaker properties compared to the bovine and porcine gelatin, which limit it use in the industry. Besides, conventional method for fish gelatin extraction required long production time. Chemical treatments are often being used in enhancing the fish gelatin yield and properties but it may leave toxic residues and may affect the amino acid content of the gelatin. High Pressure Processing (HPP) is a novel method suggested for fish gelatin extraction. The HPP method classified as green technology as it requires low electricity throughout the process. This study will discussed the impact of HPP technique on the gelatin extract from fish skin. Three types of fish skin, namely red tilapia, grouper and threadfin bream, were used. High pressure was applied at either pre-treatment in citric acid solution or during protein hydrolysis activity. Pressure was 250 MPa and pressure holding time was 10 minutes. Conventional method was done as a standard. Study found that the yield of protein extract increases, the concentration of gelatin extract increased and the pre-treatment time were reduced.